Analisis stabilitas geser dan guling pembangunan dinding penahan tanah tipe turap di Area Tangki H13 PT Pertamina EP Sangasanga Field - Norminawati Dewi; Ahmad Ridhani Noorfauzi; Hasany Reyvanza; Tekad Budiantoro (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2026)
Slope instability in oil and gas operational areas can pose significant risks to facility safety and operational continuity, particularly in hilly regions affected by surface water flow and erosion. Such conditions were identified at the H13 tank area of PT Pertamina EP Sangasanga Field, where a rapidly deployable and effective slope reinforcement system was required. This study aims to analyze the stability of a portable sheet pile retaining wall constructed from zinc plates and steel tubing pipes as an alternative temporary slope stabilization system. The analysis was carried out using Rankine theory to determine lateral earth pressure and the Broms method to evaluate the lateral capacity of the supporting piles. Soil parameters were obtained from Standard Penetration Test (SPT) data, indicating cohesive clay soil conditions with an internal friction angle of 25°, cohesion of 16 kN/m², and a unit weight of 19 kN/m³. The results show that the active earth pressure coefficient (Ka) is 0.405, producing a total bending moment of 53.115 ton·m acting on the sheet pile structure. The lateral capacity analysis indicates that the supporting piles behave as long piles and possess sufficient capacity to resist the applied lateral loads. Stability evaluation against sliding yielded a safety factor of 2.075, indicating that the system is stable and safe under the analyzed conditions. The findings demonstrate that the combination of zinc plates and steel tubing pipes can provide adequate resistance to lateral earth pressure and serve as a practical alternative for temporary slope stabilization in oil and gas operational areas. This study contributes to the limited technical knowledge regarding the application of portable sheet pile systems made from simple materials in cohesive clay soils.